2016
DOI: 10.1007/s13127-016-0313-3
|View full text |Cite|
|
Sign up to set email alerts
|

Evolution and systematics of Green Bush-crickets (Orthoptera: Tettigoniidae: Tettigonia) in the Western Palaearctic: testing concordance between molecular, acoustic, and morphological data

Abstract: The genus Tettigonia includes 26 species distributed in the Palaearctic region. Though the Green Bush-crickets are widespread in Europe and common in a variety of habitats throughout the Palaearctic ecozone, the genus is still in need of scientific attention due to the presence of a multitude of poorly explored taxa. In the present study, we sought to clarify the evolutionary relationships of Green Bush-crickets and the composition of taxa occurring in the Western Palaearctic. Based on populations from 24 disj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(36 reference statements)
1
4
0
Order By: Relevance
“…A large number of studies have shown that the morphology-based interspecific relationship is basically consistent with the interspecific relationship established by molecular data when the morphological characteristics are selected judiciously (Grzywacz et al 2017;Noguerales, Cordero & Ortego, 2018). study showed that the interspecific relationship of Nymphalidae based on wing shape and wing vein was consistent with that based on molecular data.…”
Section: Introductionsupporting
confidence: 64%
“…A large number of studies have shown that the morphology-based interspecific relationship is basically consistent with the interspecific relationship established by molecular data when the morphological characteristics are selected judiciously (Grzywacz et al 2017;Noguerales, Cordero & Ortego, 2018). study showed that the interspecific relationship of Nymphalidae based on wing shape and wing vein was consistent with that based on molecular data.…”
Section: Introductionsupporting
confidence: 64%
“…A large number of studies have shown that the morphology-based interspecific relationship is basically consistent with the interspecific relationship established by molecular data when the morphological characteristics are selected judiciously (Grzywacz et al 2017;Noguerales, Cordero & Ortego, 2018). Marín et al (2017) showed that the interspecific relationship of Nymphalidae based on wing shape and wing vein was consistent with that based on molecular data.…”
Section: Introductionmentioning
confidence: 54%
“…A large number of studies have shown that the morphology-based interspecific relationship is basically consistent with the interspecific relationship established by molecular data when the morphological characteristics are selected judiciously (Grzywacz et al, 2017;Noguerales, Cordero & Ortego, 2018). Marín et al (2017) showed that the interspecific relationship of Nymphalidae based on wing shape and wing vein was consistent with that based on molecular data.…”
Section: Introductionmentioning
confidence: 65%